Aging : growing old in church - Willimon, William H. (Grand Rapids Baker Academic, 2020)
"A seasoned pastor and church leader reflects on aging as a spiritual journey and offers practical advice on helping others with the challenges of retirement, aging, caring for the aging, and finding faith in the last quarter of life"--
Aging with Scripture -- The Storm of Aging -- Retiring with God -- Successful Aging -- With God in the Last Quarter of Life -- Growing Old in Church -- Ending in God.
Includes bibliographical references and indexes.
Keywords: Older persons -- Religious life; Aging -- Religious aspects -- Christianity